Pengaruh Strategi Pemasaran, Kualitas Pelayanan dan Nilai Nasabah terhadap Kepuasan Nasabah pada PT. Bank Capital Indonesia Tbk Cabang Wisma Kodel - Olivia S Nelwan; Tia Artika (Jurnal Ekonomi, 2018)
The objectives of this research are to know about the influence of marketing strategy, service quality and customer value to customer satisfaction in PT Bank Capital Indonesia, Tbk, Wisma Kodel Branch. This research is using quantitative model. The research used 96 samples by distributing questionnaire which consist of 28 questions and the answer of the respondent is analyzed by using SPSS 22. In validation test, reliability test, and classic assumption test, the regression expression is as follow : Y = 0.593 + 0.101 X1 + 0.462 X2 + 0.496 X3 which is the customer satisfaction (Y) variable, marketing strategy variable (X1), service quality variable (X2) and customer value variable (X3). T test shows that the marketing strategy doesn’t have significant influence to customer satisfaction. Whereas, service quality has significant influence to customer satisfaction and customer value has significant influence to customer satisfaction. The F test shows that marketing strategy, service quality, and customer value are simultaneous effecting significantly to customer satisfaction.